Comparative Analysis of Concrete Structure Bridges and Steel Structure Bridges in Terms of Economics - Marwa Nurul Khorimah Hanafi; Nurul Azizah; Salsabilla krisya Putri; Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2024)
This study compares the economic feasibility of concrete and steel bridges by analyzing material costs, maintenance expenses, and project efficiency. A comprehensive literature review highlights the advantages and limitations of each material. Concrete is recognized for its low initial cost, excellent compressive strength, and widespread availability, making it ideal for conventional bridge designs. Steel, on the other hand, offers superior tensile strength, high durability, and faster prefabrication, making it suitable for complex and long-span structures. The research methodology involves applying the Critical Path Method (CPM) for scheduling and cost analysis to determine the most efficient material choice based on project requirements. The findings reveal that while steel bridges have a higher initial cost, they may yield lower long-term maintenance expenses and greater structural adaptability. Conversely, concrete bridges are more favorable for short-term projects with immediate budget constraints. The results emphasize the importance of strategic material selection and efficient project scheduling to achieve optimal construction outcomes and cost management.